Does the social capital (really) affect entrepreneurial success? - Rahman, Hafiz; Primadona, Primadona; Elfindri, Elfindri (Piccola Impresa / Small Business, 2020)
The study aims to examine whether the social capital is really influencing entrepreneurial success of small and medium scale enterprises/SMEs in embroidery and weaving business in West Sumatra, Indonesia. Using the quantitative approach, the study was undertaken in some regions in West Sumatra Province, which are famous as the centre of SMEs in embroidery and weaving business. All SMEs operated in 8 regions were used as study population. The number are 235 of SMEs. In measuring the influence of social capital to SMEs entrepreneurial success, the SEM (Structural Equation Modeling) was used as the tool for analysis. The study has found that the social capital has the negative impact on entrepreneurial success. This is a contradictory finding with the previous studies elsewhere. A severe competition between SMEs in this business is found as the major reason of why the social capital is no longer be considered as an intangible asset that can be used in the business survival in the study context. Findings of this study has a value and originality as a discourse in the social capital topic, since many research and studies found and viewed that the social capital is one of the most prominent factors in entrepreneurial success.